2021
DOI: 10.1021/jacs.1c06654
|View full text |Cite
|
Sign up to set email alerts
|

Conformationally Switchable Silylone: Electron Redistribution Accompanied by Ligand Reorientation around a Monatomic Silicon

Abstract: Complexes that could be switched between two electronic states by external stimuli have attracted much attention for their potential application in molecular devices. However, a realization of such a phenomenon with low-valent main-group element-centered complexes remains challenging. Herein, we report the synthesis of cyclic (alkyl)(amino)silylene (CAASi)ligated monatomic silicon(0) complexes (silylones). The bis-(CAASi)-ligated silylone adopts a π-localized ylidene structure (greenish-black color) in the sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 77 publications
0
19
0
Order By: Relevance
“…Theoretical studies suggested that this compound could be viewed as a cyclic alkyl silylene‐stabilized ylidone [12] . Iwamoto and co‐workers were able to isolate the monoatomic silicon(0) complex ( IV ) with an ylidene structure by employing a cyclic (alkyl)(amino)silylene ligand [3i] . Driess et al.…”
Section: Methodsmentioning
confidence: 99%
“…Theoretical studies suggested that this compound could be viewed as a cyclic alkyl silylene‐stabilized ylidone [12] . Iwamoto and co‐workers were able to isolate the monoatomic silicon(0) complex ( IV ) with an ylidene structure by employing a cyclic (alkyl)(amino)silylene ligand [3i] . Driess et al.…”
Section: Methodsmentioning
confidence: 99%
“…[9] In addition, compounds of [L2E][X] [10] and NaECO [11] (L = two-electron donor ligand; E = P, As; X= counter anion) are two representative examples of E-atom transfer reagents. For group 14 elements, the fascinating ability of a few zero-valent silicon species, namely silylones C [12] and a base-stabilized disilicon D [13] , have been demonstrated as surrogates of elemental silicon. [14] Scheschkewitz et al showed atomically precise expansion of unsaturated silicon clusters through SiCp*2 (E) [15] and (NHC)GeCl2 (NHC = 2,3,4,5-tetramethylimidazolylidene) [16] , while the group of Wesemann disclosed a base-stabilized germasilenylidene F that delivers a Si atom.…”
Section: Introductionmentioning
confidence: 99%
“…17 In addition, compounds of [L2E][X] [18][19][20] and NaECO [21][22][23][24][25] (L = two-electron donor ligand; E = P, As; X= counter anion) are two representative examples of E-atom transfer reagents. For group 14 elements, the fascinating ability of a few zero-valent silicon species, namely silylones C 26 and a base-stabilized disilicon D 27 , have been demonstrated as surrogates of elemental silicon. 28 Scheschkewitz et al showed atomically precise expansion of unsaturated silicon clusters through SiCp*2 (E) 29 and (NHC)GeCl2 (NHC = 2,3,4,5tetramethylimidazolylidene) 30 , while the group of Wesemann disclosed a base-stabilized germasilenylidene F that delivers a Si atom.…”
Section: Introductionmentioning
confidence: 99%